Persuasive Techniques in Who Indonesia’s Infographics about Covid 19 Disease - Winaria P.L. Simanjuntak; Hestika Ginting (Budapest International Research and Critics University, 2022)
Infographics are served with visualization and define the process of perceiving and using visual information for the purpose of persuasion. This research is a descriptive qualitative study to identify the types of persuasive techniques disease and to investigate ways of using persuasive techniques used in WHO Indonesia’s infographics about covid 19. This method was carried out by working with data, organizing it, breaking it into manageable units, synthesizing it, searching for patterns, discovering the findings. Based on the result, The techniques of persuasive used in the infographics of WHO Indonesia are rationalization, identification, conformity and compensation. Those techniques use certain ways, they are: evidence, anecdote, emotive, loyalty and patriotism value, and graphs and diagram. It can be concluded that the infographics by WHO Indonesia use persuasive techniques to meet the aims that is to inform, educate, entertain, and persuade the audience to change their behavior about the Covid 19 disease.